Model Komunikasi Orang Tua untuk Kecerdasan Emosional dan Spiritual Anak dalam Membangun Generasi Emas di Medan - Delima, Wirda; Lahmuddin Lubis (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Abstract The Golden Generation is a generation that has high intelligence, character and competitiveness. One important factor in forming the Golden Generation is to provide children with emotional and spiritual intelligence. This emotional and spiritual intelligence will help children develop themselves as a whole and be able to face various challenges in life. Parental communication has an important role in child development, including the development of emotional and spiritual intelligence. An effective parental communication model can help children in several ways, including: 1. Developing self-confidence 2. Learning to manage emotions 3. Building positive relationships with other people 4. Developing moral and spiritual values. This research uses qualitative method with a case study approach. Data was collected through in-depth interviews with parents and children in Medan. The research results show that there are several models of parental communication that are effective in building children's emotional and spiritual intelligence in Medan. Some of these models include: 1. Open and honest communication 2. Communication that is full of love and attention 3. Communication that provides support and encouragement 4. Communication that is based on moral and spiritual values ​​Effective parental communication models have a role important in forming the emotional and spiritual intelligence of children in Medan. By giving children emotional and spiritual intelligence, we can help them develop themselves holistically and be able to face various challenges in life. This will ultimately contribute to the formation of a Golden Generation in Medan.